Comparative Electro-Thermal Mathematical Modeling of Transient Temperature Distribution in Pouch and Cylindrical Li-Ion Battery Cells - Eko Andi Prasetyo; Damora Rhakasywi; Fahrudin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2026)
The increasing rate of internal heat accumulation during high-power discharge represents a major challenge in the design of Battery Thermal Management Systems (BTMS) for electric vehicles. Battery cell geometry plays a significant role in determining heat propagation pathways and heat dissipation characteristics. This study aims to conduct a comparative evaluation of the transient temperature distribution between cylindrical and pouch Lithium-ion battery cells using a one-dimensional (1D) electro-thermal mathematical model. The model was developed based on the principles of energy conservation and the Bernardi heat generation equation and was numerically solved using the Finite Difference Method (FDM) with an Explicit Euler scheme implemented in Python. Simulations were performed under various discharge rates (1C, 3C, and 5C). The results indicate that cylindrical cells are highly susceptible to the core thermal trapping phenomenon, reaching a maximum core temperature of 52.64°C at a 5C discharge rate, whereas the maximum core temperature of pouch cells was limited to 50.61°C under the same operating condition. Furthermore, the larger surface-area-to-volume ratio of pouch cells resulted in lower and more uniform surface temperature profiles. The developed 1D model was successfully validated against published three-dimensional finite element simulation data, yielding prediction errors ranging from 0.09% to 1.12%. Overall, the findings indicate that the proposed comparative 1D model provides reliable temperature predictions while requiring relatively low computational effort, making it a practical option for preliminary thermal analysis and battery pack design in electric vehicle applications.